Impact of Coronavirus Disease of 2019 Vaccine on Health and Physical Activities Among Physical Education Students in China - Ahmed Laar, Rizwan; Zhang, Zhengyi; Menhas, Rashid; Zhang, Lei; Zhu, Shicheng; Fan, Xin; Wang, Wei; Li, Shumin (Frontiers in Public Health, 2022)
Abstract Purpose: This research focused primarily on the impact of the COVID-19 vaccine (Vero) on Chinese physical education (PE) students' health and physical activity (PA) performance. Methods: This study used quantitative methods and phenomenological procedures to collect and analyze data. Survey techniques were the main method used for collecting data from Chinese university students, using a self-designed questionnaire with a Cronbach's alpha α value of 0.76. To ensure the quality of the study, confirmatory factor analyses (CFA) were conducted and the internal consistency reliability of the instrument was measured (alpha coefficient = 0.82). In addition, using factor loadings with h2 and an independent-sample t-test, we analyzed the responses of the 443 participants (n = 443 with a response rate of 90.40). Results: Most participants (around 94%) did not experience any adverse reactions that impacted their daily life activities, health, or performance during physical activity. However, about 30% to 40% of students felt lethargy, weakness, muscle pain, or swelling. With regard to the impact of the vaccine on daily life, there was no difference in the responses between participants who had only received one shot of the COVID-19 vaccine and those who had received two shots (p>.05 in most cases). Conclusion: The study concluded that the COVID-19 vaccine had no significant effect on daily activities, health, and PA performance of PE students. The results of this study could be used by policy makers to encourage people to get vaccinated and eradicate the isolation caused by COVID-19 which leads many people to develop various non-communicable diseases (NCDs).